2017
DOI: 10.1002/polb.24314
|View full text |Cite
|
Sign up to set email alerts
|

A novel shape memory poly(ε-caprolactone) network via UV-triggered thiol-ene reaction

Abstract: A facile method to prepare shape memory polymers crosslinked by SiO2 is described. A series of biodegradable shape memory networks were obtained through thiol‐ene reaction triggered by UV irradiation between surface‐thiol‐modified SiO2 nanoparticles and end‐acrylate poly (ε‐caprolactone) (PCL). The highly selective thiol‐ene reaction ensured a uniform distribution of PCL chains between crosslinkers, contributing well‐defined network architecture with enhanced mechanical and shape‐memory properties. Thiol‐funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…With the addition of 0.5 mol% DPAB, the reaction can perform quickly under visible light irradiation. Yang et al [ 58 ] reported a rapid start/stop thiol–ene reaction by turning on‐off the UV source, which produced a series of biodegradable shape memory materials. It can be seen from Figure that the growth of polymer chains in the light‐on periods followed a linear relationship between the M n and reaction time, whereas no M n growth was observed during the dark periods.…”
Section: Resultsmentioning
confidence: 99%
“…With the addition of 0.5 mol% DPAB, the reaction can perform quickly under visible light irradiation. Yang et al [ 58 ] reported a rapid start/stop thiol–ene reaction by turning on‐off the UV source, which produced a series of biodegradable shape memory materials. It can be seen from Figure that the growth of polymer chains in the light‐on periods followed a linear relationship between the M n and reaction time, whereas no M n growth was observed during the dark periods.…”
Section: Resultsmentioning
confidence: 99%
“…The initial length was recorded as ɛ o , the sample was heated in a 60 °C water bath at a constant temperature for 1 min, then stretched to 200% (the length obtained was recorded as ɛ m ), cooled to room temperature, with an isothermal time of 1 min, unloaded external forces (the length after removal of load was recorded as ɛ u ), then placed into 60 °C hot water to recover its original shape (the length was recorded as ɛ p ), the shape memory test of all samples was repeated for three times. The shape recovery ratio ( R r ) and the shape fixity ratio ( R f ) were calculated by the following equations Rr=ɛuɛPɛuɛo×100% Rf=ɛuɛoɛmɛo×100% …”
Section: Methodsmentioning
confidence: 99%
“…Considerable research has been devoted to the development of novel BSMP formulations that have the potential for use in medicine. For recent examples we direct the reader to the following references . In the Becker lab, we have developed amino acid‐based poly(ester urea)s (PEUs) and explored their shape memory behavior .…”
Section: Future and Outlookmentioning
confidence: 99%